Green-tea-synthesized silver nanoparticles as a sensing platform for determination of tetracycline in honey samples - Pistonesi, Denise Belén (2021)
Background: Silver nanoparticles (AgNPs) can be easily obtained in aqueous solutionby chemical reduction using appropriate reducing agents and stabilizers. Thedevelopment of environmentally-friendly methods using non-toxic solvents and reagentshas become an alternative for the synthesis of these particles and their future applicationas sensor probe for agricultural products. In this work a straightforward method basedon green tea extracts as reducing and capping agent is proposed for the synthesis ofAgNPs, followed by their evaluation as sensing platform for determination of tetracyclinein honey samples.Results: Highly-stable nanoparticles were easily obtained by combining green teaaqueous extracts and ultrasound irradiation during 2 min. The as-synthesized AgNPs,spherical in shape and with average size of 8.5 nm, were evaluated for determination oftetracycline by following the changes on the localized surface plasmon resonance band(LSPR) at 450 nm induced by the presence of this antibiotic at pH= 5.8. The method wassuccessfully applied in the concentration range between 200 and 800 μg L-1 with R2 >0.996 and limit of detection (LOD) of 52.7 μg L-1. Multiple honey samples were analyzedand obtained recovery values were ranged between 82.8 ? 116 %, with relative standarddeviation values lower than 6.69%.Conclusion: Obtained results demonstrate the synthesized AgNPs, only using greentea extracts, represents a promising and sustainable alternative tool for the cost-effectivedetermination of tetracycline antibiotics in honey.